Impact of In Situ Soil in Soil-Bentonite Cutoff Wall Backfill on Compressibility and Hydraulic Conductivity. (20th January 2021) - Fan, Ridong; Yang, Yuling; Liu, Songyu
Abstract : Soil-bentonite cutoff walls, consisting of excavated in situ soil and bentonite as backfills, are used extensively as vertical barriers for groundwater pollution control. Sand mixed with high-quality natural sodium bentonite (NaB) is commonly used as a research object to investigate the hydraulic and compression properties of soil-bentonite backfills. However, pure sand could rarely be found in real conditions, and natural NaB may not be available readily in some countries such as China, India, and Turkey. This paper presents a comprehensive laboratory investigation on the compressibility and hydraulic conductivity ( k ) of soil-bentonite backfills created by simulated in situ soil and low-quality sodium activated calcium bentonite (SACaB). The simulated in situ soils are prepared using sand-natural clay mixtures with sand to natural clay mass ratios ranging from 0.5 to 6.0, and the bentonite content ( BC ) in the base mixture ranges from 0 to 15%. The result indicates that BC dominates the compression index ( C c ) of the backfill, and a unique relationship between void ratio at effective vertical compression stress of 1 kPa and compression index is proposed for various types of soil-bentonite backfills. An increase in either BC or clay size fraction ( CF ) in simulated in situ contributes to reducing k, but the impact of CF in simulated in situ soil on k tends to be insignificant for backfill with BC higher than 6%. A new characteristic parameter based on the concept of void ratio of bentonite ( e b ), named apparent void ratio of clay size fraction ( e C ), is developed for predicting soil-bentonite backfills created by in situ soils and bentonites with various contents.